Angioedema recorrente – caso clínico - Martins, Sandrina (2014)
Introduction: Hereditary angioedema (HA) is a rare cause of recurrent angioedema caused by a default in the gene that encodes the C1 esterase inhibitor (C1-INH). The oedema involves predominantly the face, limbs and genital and gastrointestinal tract. The involvement of the larynx, although less frequent, is the most severe clinical expression of HA and is potentially fatal. Case report: Clinical report of an eight-year-old female with multiple episodes of angioedema. The laboratory study confirmed the diagnosis of HA. Discussion: HA diagnosis is established based on the clinical history, family history and complements testing. Its documentation is extremely important because it is potentially fatal and needs specific therapy.